The Synthesis of the Arts: From Ceremonial Ritual to “Total Work of Art” - Brown, Steven; Dissanayake, Ellen (Frontiers in Sociology, 2018)
The 19th century notion of a Gesamtkunstwerk or “total work of art” referred to a performance spectacle that synthesized multiple forms of the arts into a unified work, often times taking place in a grand setting that befit the spectacle. Such a performance would be a quasi-religious ceremony occurring in a location akin to a temple. We argue here that, long before aesthetic theorists devised the notion of a total work of art, religious ceremonies themselves showed all of the key features of a Gesamtkunstwerk. In fact, we propose that ceremonial rituals are essentially assemblages of arts-related behaviors and objects, and that this observation provides the historical and cognitive underpinnings for what would later become the total work of art in aesthetic practice. An important implication of this argument is that religion and the arts co-evolved during the course of human history.